Experiment and numerical analysis of prestressed unequal-walled rectangular concrete-filled steel box beams - Qi Su; Guangyuan Fu; Jian Yang; Siping Li (Scientific Reports)
Abstract When long-span beams undergo large, the strength of the beam material cannot be fully utilized. To solve this problem, a prestressed unequal-walled rectangular concrete-filled steel box (PURCFSB) beam is proposed in this paper. The prestressing is added to the concrete-filled steel tubular (CFST) beam and the section is designed. This beam is an improved concrete-filled steel tubular (CFST) beam with flanges of unequal thickness; the upper part of the steel box contains concrete, and the lower part is fitted with prestressed steel bars. Bending tests on ten PURCFSB beams with different concrete filling ratios and prestress levels revealed that prestressing can increase the yield bending moment and delay the cracking of concrete. The appropriate filling ratio can improve the structure’s yield moment and ultimate bearing capacity and reduce its self-weight while avoiding concrete cracking within the scope of work. Finite element analysis of the whole bending process of PURCFSB beams, carried out using ABAQUS software, yields results that are in good agreement with the experimental results. Parametric analysis (based on the validated finite element model) of the effects of the filling ratio and prestress level on the bending performance revealed that PURCFSB beams have good bearing capacity and deformation performance.